2023
DOI: 10.3389/fimmu.2023.1098741
|View full text |Cite
|
Sign up to set email alerts
|

Partial immune responses in Sichuan bream (Sinibrama taeniatus) after starvation

Abstract: BackgroundFood deprivation is a severe stress across multiple fields and it might be a challenge to immune system.MethodsIn the present study, adult male Sinibrama taeniatus were deprived of feed for 7 to 28 days. We explored the effects of starvation on immunity in S. taeniatus through hematological analysis, antioxidant capacity analysis, detection of the content or activity of immune factors in plasma, and transcriptomic analysis.ResultsThe results indicated that biometric indexes significantly decreased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Many studies have been clearly elaborated that the starvation or food-deprived often influenced the function of immunity in mammals (Han et al, 2021;Loft et al, 2022;Forslund, 2023;Janssen et al, 2023) and altered their energy metabolism (Browning et al, 2012;Soeters et al, 2012;Dote-Montero et al, 2022). Similarly, the aforementioned phenomena have also been observed in teleosts (Dai et al, 2018;Liao et al, 2021;Wang et al, 2021;Gou et al, 2023;Shi et al, 2023). Moreover, although some studies have shown that starvation alters the expression of the autophagy-related genes in fish (Balmori-Cedeño et al, 2019;Wu et al, 2020;Pan et al, 2022), there are still many autophagy-related gene from teleosts that have not been identified and characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been clearly elaborated that the starvation or food-deprived often influenced the function of immunity in mammals (Han et al, 2021;Loft et al, 2022;Forslund, 2023;Janssen et al, 2023) and altered their energy metabolism (Browning et al, 2012;Soeters et al, 2012;Dote-Montero et al, 2022). Similarly, the aforementioned phenomena have also been observed in teleosts (Dai et al, 2018;Liao et al, 2021;Wang et al, 2021;Gou et al, 2023;Shi et al, 2023). Moreover, although some studies have shown that starvation alters the expression of the autophagy-related genes in fish (Balmori-Cedeño et al, 2019;Wu et al, 2020;Pan et al, 2022), there are still many autophagy-related gene from teleosts that have not been identified and characterized.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, starvation stress is considered to be one of the most important intrinsic factors that not only alters the immune function (Tran et al, 2018;Song et al, 2019;Liao et al, 2021), but also changes basic energy metabolism in teleosts (Dai, W. et al, 2018;Dar et al, 2019;Florescu Gune et al, 2019;Martin et al, 2010). For instance, in Sinibrama taeniatus, the innate immune parameters were increased, but the adaptive immune index was declined after short period of starvation (Shi et al, 2023). In addition, starvation changes the plasma glucose level and increased lysozyme levels in Anguilla anguilla (Caruso et al, 2010).…”
Section: Introductionmentioning
confidence: 99%